Renewal : Remaking America's Schools for the Twenty-First Century. - Kwalwasser, Harold (R & L Education, 2012)
Renewal offers a clear picture of how to move away from the mass-production style of education that most schools offered throughout the twentieth century to a new, more innovative, and flexible model that can meet this country's promise of truly educating every child and preparing each of them for the challenges ahead.